Vanádio no material particulado atmosférico na região de ressurgência de Cabo Frio-RJ - Neves, Alessandra Fortuna (2007)
In the present work atmospheric particles were collected in the municipal districts of Arraial do Cabo and Rio Bonito, both located in Rio de Janeiro State, during the period of February of 2004 to January of 2005. The chosen collection points were the Institute of Studies of the Sea Almirante Paulo Moreira (IEAPM), located in front of the Beach of the Angels and in the square of a booth toll in the Via Lagos. The samples were collected in glass fiber filters using a High-Vol equipment (Sibata HVC-500, Japan) and immediately conditioned in dissecador. The filters were cutted in pieces and digested in a microwave oven. The extracts obtained after digestion was used in order to determine metals concentration by ICP-AES (Ca, Cu, Mo, Mn, Ti, V e Zn) and FAAS (K). The results obtained revealed that PTS levels in the IEAPM (23,1-659 mg/m3) are higher than the ones obtained in the Via Lagos (25,4-55,6 mg/m3), due to marine influence, which is responsible for coarser particles emission. Between elements V was the only one that showed higher concentration levels in the IEAPM (0,840-20,9 ng/m3) when compared to Via Lagos. Highest values of V concentration in this sampling site was obtained during upwelling events, indicating that this phenomena has an influence in the presence of atmospheric vanadium. PCA analysis was able to identify the main sources of particulate in the atmosphere distributed in four principal factors. In the IEAPM sampling point two sources (crustal and marine) were identified which are responsible for 86,5% of the total variance of the data. In the Via Lagos sampling points only one anthropogenic source (due to vehicle traffic) was identified, which is responsible for 89,2% of the total variance of the data. The results showed that a positive and significant association between V, Mo and Zn in the IEAPM strongly indicates a common marine source of these elements in the atmosphere. Moreover, the lowest Cu values, obtained during upwelling events, are associated to its inhibiting function in primary production. In the booth toll of Via Lagos, results from principal component analysis revealed that the presence of Ca, Mn, Mo, Ti, V, Cu and Zn in the atmosphere are related to vehicle exhaust; emitted by lubricant oils vapours, while Cu comes from braking manoeuvres.